Redirection of Cord Blood T Cells and Natural Killer Cells for Elimination of Autologous HIV-1-Infected Target Cells Using Bispecific DART® Molecules - Pollara, Justin; Edwards, R. Whitney; Jha, Shalini; Lam, Chia-Ying Kao; Liu, Liqin; Diedrich, Gundo; Nordstrom, Jeffrey L.; Huffman, Tori; Pickeral, Joy A.; Denny, Thomas N.; Permar, Sallie R.; Ferrari, Guido (Frontiers in Immunology, 2020)
Mother-to-child transmission of HIV-1 remains a major global health challenge. Currently, HIV-1-infected infants require strict lifelong adherence to antiretroviral therapy to prevent replication of virus from reservoirs of infected cells, and to halt progression of disease. There is a critical need for immune interventions that can be deployed shortly after infection to eliminate HIV-1-infected cells in order to promote long-term remission of viremia, or to potentially cure pediatric HIV-1-infection. Bispecific HIV x CD3 DART® molecules able to co-engage the HIV-1 envelope protein on the surface of infected cells and CD3 on cytolytic T cells have been previously shown to eliminate HIV-1 infected cells in vitro and are candidates for passive immunotherapy to reduce the virus reservoir. However, their potential utility as therapy for infant HIV-1 infection is unclear as the ability of these novel antibody-based molecules to work in concert with cells of the infant immune system had not been assessed. Here, we use human umbilical cord blood as a model of the naïve neonatal immune system to evaluate the ability of HIV x CD3 DART molecules to recruit and redirect neonatal effector cells for elimination of autologous CD4+ T cells infected with HIV-1 encoding an envelope gene sequenced from a mother-to-child transmission event. We found that HIV x CD3 DART molecules can redirect T cells present in cord blood for elimination of HIV-infected CD4+ T cells. However, we observed reduced killing by T cells isolated from cord blood when compared to cells isolated from adult peripheral blood —likely due to the absence of the memory and effector CD8+ T cells that are most cytolytic when redirected by bispecific DART molecules. We also found that newly developed HIV x CD16 DART molecules were able to recruit CD16-expressing natural killer cells from cord blood to eliminate HIV-infected cells, and the activity of cord blood natural killer cells could be substantially increased by priming with IL-15. Our results support continued development of HIV-specific DART molecules using relevant preclinical animal models to optimize strategies for effective use of this immune therapy to reduce HIV-1 infection in pediatric populations.